The Economic Impact of COVID-19 Treatment at a Hospital-level: Investment and Financial Registers of Brazilian Hospitals - Ana Paula Beck da Silva Etges; Ricardo Bertoglio Cardoso; Milena S Marcolino; Karen Brasil Ruschel; Ana Paula Coutinho; Elayne Crestani Pereira; Fernando Anschau; Fernando Aranha; Filipe Carrilho; Giovanna Vietta; Gisele Alsina Nader Bastos; Joanna d’Arc Lyra Batista; et al. (Journal of Health Economics and Outcomes Research)
**Background:** The economic impact associated with the treatment strategies of coronavirus disease-2019 (COVID-19) patients by hospitals and health-care systems in Brazil is unknown and difficult to estimate. This research describes the investments made to absorb the demand for treatment and the changes in occupation rates and billing in Brazilian hospitals.